Local Action for Realizing Sustainable Society: A Survey of Japanese "Futurecity" Initiative - Marina Takeyasu; Haisong Nie; Dawei Gao; Chuangbin Chen (International Journal of Agriculture System, 2018)
To convert a society to a sustainable system, attempts are required not only at international and governmental levels, but also at regional levels. It is necessary to challenge multiple issues through cooperation among various actors, such as national governments, local governments, private enterprises and residents. In Japan, one of the initiatives to achieve “the sustainable” at regional level is the “FutureCity” initiative. This is a part of National Strategic Projects in “New Growth Strategy”, which Japanese government introduced in 2010. The purpose of the “Futurecity” initiative is to create the capacity in cities to deal with environmental issues and problems of aging society, as well as establishing sustainable socioeconomic system with environmental aspects, social aspects and economic aspects. Japanese government selected, as the “FutureCity”, the five cities (Yokohama city, Shimokawa town, Kashiwa city, Toyama city and Kitakyusyu city) for making pioneering effort on these challenges, and the six cities that were hit by the Great East Japan Earthquake and great Tsunami in 2011. This “Future city” is expected to provide model solution of human common issues as a forerunner. The object of this research is to define the current situations and problems of the “FutureCity” initiative, through a case study on Yokohama city in Kanagawa prefecture, which is characterized as a big city in Japan. Here, we examined how Yokohama city is tackling the environmental issues and problems of aging society as the “FutureCity” and what problems it has in maintaining their initiative itself as a local government. In addition, we considered how, at international level, Japanese “FutureCity” initiative can contribute to realizing sustainable society